Application of Endophytic Pseudomonas fluorescens and a Bacterial Consortium to Brassica napus Can Increase Plant Height and Biomass under Greenhouse and Field Conditions - Lally, Richard D.; Galbally, Paul; Moreira, António S.; Spink, John; Ryan, David; Germaine, Kieran J.; Dowling, David N. (Frontiers in Plant Science, 2017)
Plant associated bacteria with Plant Growth Promotion (PGP) properties have been proposed for use as environmentally friendly biofertilisers for sustainable agriculture, however, analysis of their efficacy in the field is often limited. In this study, greenhouse and field trials were carried out using individual endophytic Pseudomonas fluorescens strains, the well characterised rhizospheric P. fluorescens F113 and an endophytic microbial consortium of 10 different strains. These bacteria had been previously characterised with respect to their PGP properties in vitro and had been shown to harbor a range of traits associated with PGP including siderophore production, 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity and inorganic phosphate solubilisation. In greenhouse experiments individual strains tagged with gfp and Kmr were applied to Brassica napus as a seed coat and were shown to effectively colonize the rhizosphere and root of B.napus and in addition they demonstrated a significant increase in plant biomass compared to the non-inoculated control. In the field experiment the bacteria (individual and consortium) were spray inoculated to winter oilseed rape B. napus var. Compass which was grown under standard North Western European agronomic conditions. Analysis of the data provides evidence that the application of the live bacterial biofertilisers can enhance aspects of crop development in Brassica napus at field scale. The field data demonstrated statistically significant increases in crop height, stem/leaf and pod biomass, particularly, in the case of the consortium inoculated treatment. However, although seed and oil yield were increased in the field in response to inoculation, these data were not statistically significant under the experimental conditions tested. Future field trials will investigate the effectiveness of the inoculants under different agronomic conditions.